Material Witness and Material Injustice - Ronald L. Carlson; Mark S. Voelpel (Washington University Law Quarterly, 1980)
No serious student of the adversary system can ignore the grave threat to the integrity of the American witness process posed by this nation's material witness statutes.
Keywords: Witness procedure; Witness detention; Witnesses; United States